The Dynamics of Poverty : Why Some People Escape from Poverty and Others Don't? An African Case Study - Kanbur, Ravi, 1954- 28.08.1954- (The World Bank, 1999)
August 1995 - In urban areas of Côte d'Ivoire, human capital is the endowment that best explains welfare changes over time. In rural areas, physical capital - especially the amount of land and farm equipment owned - matters most. Empirical investigations of poverty in developing countries tend to focus on the incidence of poverty at a particular point in time. If the incidence of poverty increases, however, there is no information about how many new poor have joined the existing poor and how many people have escaped poverty. Yet this distinction is of crucial policy importance. The chronically poor may need programs to enhance their human and physical capital endowments. Invalids and the very old may need permanent (targeted) transfers. The temporarily poor, on the other hand, may best be helped with programs that complement their own resources and help them bridge a difficult period. Results from analyses of panel surveys show significant mobility into and out of poverty and reveal a dynamism of the poor that policy should stimulate. Understanding what separates chronic from temporary poverty requires knowing which characteristics differentiate those who escape poverty from those who don't. In earlier work, Grootaert, Kanbur, and Oh found that region of residence and socioeconomic status were important factors. In this paper they investigate the role of other household characteristics, especially such asset endowments as human and physical capital, in the case of Côte d'Ivoire. In urban areas of Côte d'Ivoire, human capital is the most important endowment explaining welfare changes over time. Households with well-educated members suffered less loss of welfare than other households. What seems to have mattered, though, is the skills learned throug workers too much toward a formal labor market in a time when employment growth came almost entirely from small enterprises.